2021
DOI: 10.3389/fmicb.2021.644013
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization and Whole-Genome Analysis of a Novel Bacteriophage HCF1 Infecting Citrobacter amalonaticus and C. freundii

Abstract: Citrobacter species often occur in sewage, food, soil, wastewater, and in the intestinal tract of animals and humans. Citrobacter spp. cause urinary tract infections (UTIs) and infantile meningitis in humans. Due to the presence of plasmid-encoded resistance genes, Citrobacter spp. are often resistant to many antibiotics. In this study, Citrobacter virus HCF1, a novel virulent bacteriophage capable of killing Citrobacter amalonaticus and Citrobacter freundii, was isolated from the sewage water. The isolated ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…Phylogenetic analysis revealed that our isolated strain GDZQ201912 showed a very close association with other strains of C. freundii submitted from China and UK and formed separate clades with other Citrobacter sp., such as C. portucalensis (AP022399.1, AP022486.1, and AP022513.1). The physiological and biochemical profiles of strain GDZQ201912 were similar to those of other isolates reported by earlier works [ 49 , 50 ]. Variations in the biochemical test, such as those of tyrosine, putrescine [ 38 ], indole, citrate, H 2 S, malonate, raffinose, and dulcitol, were also described by earlier studies [ 17 , 49 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Phylogenetic analysis revealed that our isolated strain GDZQ201912 showed a very close association with other strains of C. freundii submitted from China and UK and formed separate clades with other Citrobacter sp., such as C. portucalensis (AP022399.1, AP022486.1, and AP022513.1). The physiological and biochemical profiles of strain GDZQ201912 were similar to those of other isolates reported by earlier works [ 49 , 50 ]. Variations in the biochemical test, such as those of tyrosine, putrescine [ 38 ], indole, citrate, H 2 S, malonate, raffinose, and dulcitol, were also described by earlier studies [ 17 , 49 ].…”
Section: Discussionsupporting
confidence: 85%
“…In the case of pathogenic bacteria, such as C. freundii , multidrug resistance is one of the most prominent problems [ 50 ]. In this study, the isolated strain was resistant to four different β-lactam antibiotics, including ampicillin, clindamycin, lincomycin, and penicillin.…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed in another study which reported that pSf-2 phage produced clear plaques only in S. flexneri cultures (ATCC 12022, 11 836 and 29903) 56 . Similarly, a more recently described phage (HCF1) 58 belonging to Drexlerviridae family displayed lytic activity against two Citrobacter species ( C. freundii and C. amalanoticus ) but not against S. dysenteriae. In contrast, Hamdi et al 55 reported that S. flexneri and E. coli can be lysed by Drexlerviridae phage SH6 and Sfin-1.…”
Section: Resultsmentioning
confidence: 90%
“…For example, from 2015 to 2019, the Kuty Everett GF team uploaded 9 complete genome sequences of C. freundii phage (Moogle, Merlin, Maleficent, Maroon, Mijalis, Moon, Michonne, Mordin, and Miller) (46)(47)(48)(49)(50)(51)(52)(53)(54), which were similar to vB_CbrM_HP1, but they did not further study their biological characteristics or antibacterial activities in vivo or in vitro. Only five Citrobacter phages (C. freundii phage IME-JL8, LK1, phiCFP-1, CfP1, and HCF1) have been characterized thus far (19)(20)(21)(22)(23). Research suggested that they were Siphoviridae phages (IME-JL8 and HCF1), Podoviridae phages (LK1 and phiCFP-1), or a Myovirus phage (CfP1).…”
Section: Discussionmentioning
confidence: 99%
“…There are approximately 40 Citrobacter phages published in PubMed. Only five Citrobacter phages (C. freundii phage IME-JL8, LK1, phiCFP-1, CfP1, and HCF1) have been characterized thus far (19)(20)(21)(22)(23). C. freundii phage IME-JL8 was used to study the antimicrobial activity in carp both in vivo and in vitro (19).…”
Section: Introductionmentioning
confidence: 99%